Thromboembolism in Newborns, Infants and Children - Nowak-Göttl, Ulrike; Kosch, Andrea; Schlegel, Nicole (Thrombosis and Haemostasis, 2001)
As in adults, acquired and inherited prothrombotic risk factors increase the risk of thrombosis in neonates, infants and children. Duplex sonography, venography, computed tomography and magnetic resonance imaging can be used to diagnose childhood thromboembolism, but venography is the recommended method to confirm vascular occlusion of the upper venous system. After suffering thrombosis, patients should be screened for factor V G1691A, prothrombin G20210A and MTHFR C677T genotypes, deficiencies of protein C, protein S, and antithrombin, elevation of lipoprotein (a) and fasting homocysteine concentrations (3 to 6 months after thrombotic onset: plasma-based assays). Data interpretation is based on age-dependent reference ranges and the identification of causative gene mutations/polymorphisms with respect to the individual ethnic background. Paediatric treatment protocols for acute thromboembolism, including thrombolytic and anticoagulant therapy, are hampered by the lack of appropriate clinical trials. Thus, recommendations from small-scale studies in paediatric patients and guidelines adapted from adult patient protocols may be helpful in the management of paediatric patients on an individual patient basis.
Keywords: Paediatric venous thrombosis; ischaemic stroke; acquired and genetic prothrombotic risk factors; lipoprotein (a); anticoagulant therapy